Learning the hard way: 10 lessons for developing undergraduate curricula. Issue 12 (December 2016) - Jacob, Hannah; Fertleman, Caroline R
Abstract: The present study outlines key learning points derived from 2 years spent developing a national undergraduate curriculum for child health. Findings are sourced from analyses of a series of semi‐structured musings by beleaguered educationalists and may serve to reassure others engaged in developing undergraduate curricula that it is possible to survive the process and even to produce something quite good. The authors' best advice is to do it, but don't say we didn't warn you. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.